Environmental sustainability governance in mega sport events: insights from FIFA world cup 2022 practices - Yao, F.; Wang, P.; Liu, B.; Guo, Z. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
Introduction Multiple stakeholders are highly involved in environmental sustainability governance when holding mega sports events, as governance subjects to influence governance outcomes. Therefore, it is necessary to summarize an environment sustainability governance model in a mega event, especially from the collaborative stakeholder perspective. This paper aims to analyze how stakeholders collaborate upon environmental sustainability issues in the case of FIFA World Cup Qatar 2022 (FWC 2022). Methods Original materials of this empirical case study are derived from open sources, including academic journals and book chapters, official reports and documents from FIFA and FWC 2022, media releases etc. We proceed with these materials in three steps. Firstly, providing explanation of the SFIC analytical framework. Secondly, categorizing the stakeholders of FWC 2022, and extracting the four governance elements in line with that in the SFIC model. Thirdly, concluding a framework for future mega sports events on environmental sustainability governance. Results According to SFIC collaborative governance model, it divides collaborative governance into four main stages: starting conditions (S), leadership facilitation (F), institutional design (I), collaboration process (C) and followed governance outcomes. FWC 2022 has showed a typical example of applying stakeholder collaborative governance in environmental sustainability practices. Starting with stakeholder identification stage, the critical tournament stakeholders can be identified into internal and external groups. In the leadership facilitation stage, sustainability management system (SMS) is established for clear leadership roles, responsibilities, and governance structures. In the institutional design stage, the sustainability policy and strategy were designed as the fundamental guide of the tournament and formed the basis of the SMS and stakeholder engagement. Followed the collaboration process, stakeholder collaborative governance practices on environmental sustainability are achieved through trust building with dialogue, commitment based on a materiality assessment, shared understanding on sustainability vision and missions, collaborative behaviors and outcomes on sustainable building, low-emission solutions, waste and water management. Discussion Extracting insights from the case of FWC 2022, the stakeholder collaborative governance framework can be a valuable reference for future environmental sustainability efforts in mega sports events. The initial element of the framework is to identify relevant stakeholders, then build governance structure with facilitate leadership and clear rules, for achieving the collaborative governance as an iterative process of dialogue, trust, commitment, understanding factors. It is also important to note here that the realization of a collaborative stakeholder governance process cannot be achieved in the short term but requires prior planning and preparation.